Burkitt lymphoma-related TCF3 mutations alter TCF3 alternative splicing by disrupting hnRNPH1 binding. Issue 10 (2nd October 2020) - Yamazaki, Takashi; Liu, Lizhi; Conlon, Erin G.; Manley, James L.
ABSTRACT: Burkitt lymphoma (BL) is an aggressive B-cell lymphoma characterized by translocation and deregulation of the proto-oncogene c-MYC. Transcription factor 3 (TCF3) has also been shown to be involved in BL pathogenesis. In BL, TCF3 is constitutively active, and/or expression of its transcriptional targets are altered as a result of BL-associated mutations. Here, we found that BL-related TCF3 mutations affect TCF3 alternative splicing, in part by reducing binding of the splicing regulator hnRNPH1 to exon 18b. This leads to greater exon 18b inclusion, thereby generating more of the mutated E47 isoform of TCF3. Interestingly, upregulation of E47 dysregulates the expression of TCF3 targets PTPN6, and perhaps CCND3, which are known to be involved in BL pathogenesis. Our findings thus reveal a mechanism by which TCF3 somatic mutations affect multilayered gene regulation underlying BL pathogenesis.